2021
DOI: 10.3390/ani11020315
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Brown Algae as a Potential Environmental Enrichment Material in Growing Pigs

Abstract: In barren housing conditions, enrichment materials are given to pigs to improve their welfare. Here, we assessed the suitability of an algae-based cylinder as an enrichment material on the behavioral, physiological, health and productivity welfare indicators of pigs. Algae was compared with metal chains and wood logs. The study involved 444 pigs from two successive batches on one single farm. During the suckling period, half of the pigs received algae and the control pigs received no material. After weaning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…Our results on weaner FCR are consistent with the findings of Beattie et al, 2000 , van de Weerd et al, 2006 . However, they contrast the results of other studies which did not find any significant effect of edible enrichment on FCR ( Ruiterkamp, 1987 , Lyons et al, 1995 , Peeters et al, 2006 , Munsterhjelm et al, 2009 , Averós et al, 2010 , Nannoni et al, 2016 , Nannoni et al, 2018 , Ipema et al, 2021 , Pol et al, 2021 ). Organic enrichment has been found to have positive effects on pig gut microbiota, which in turn affects the way feed is utilised ( Wen et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results on weaner FCR are consistent with the findings of Beattie et al, 2000 , van de Weerd et al, 2006 . However, they contrast the results of other studies which did not find any significant effect of edible enrichment on FCR ( Ruiterkamp, 1987 , Lyons et al, 1995 , Peeters et al, 2006 , Munsterhjelm et al, 2009 , Averós et al, 2010 , Nannoni et al, 2016 , Nannoni et al, 2018 , Ipema et al, 2021 , Pol et al, 2021 ). Organic enrichment has been found to have positive effects on pig gut microbiota, which in turn affects the way feed is utilised ( Wen et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…However, this is not consistent either with our results on decreased ear lesions in E weaners or with the results of Ko et al 2020 who found that pigs provided with enrichment toys had decreased salivary amylase concentrations on day 1 and 2 postweaning, and decreased cortisol concentrations on day 2 ( Ko et al, 2020 ). Pol et al (2021) did not find any difference between S pigs and pigs which were provided with compressed algae on salivary cortisol concentrations postweaning, and Nannoni et al (2018) did not find any significant differences in hair cortisol concentrations of pigs provided with a chain, wooden logs, or a vegetable edible block. However, sawdust, natural hemp ropes, and rubber balls were found to decrease hair cortisol concentrations in pigs ( Casal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In Lewis et al (64), all piglets could access the shredded paper provided as enrichment at the same time (as it could be removed from a box), but only a limited number of piglets could access the rope at any one time. In a study by Pol et al (101), an algae cylinder provided during the suckling period did not affect lesion scores (although lesion scores only included an ear assessment). The study found that overall, this type of object was of marginal enrichment interest to the pigs, similar to a non-effective metal chain (102).…”
Section: The Role Of Environmental Enrichmentmentioning
confidence: 96%